Rivals ebook - Cooper, Jilly (2024)
Now an original streaming series on Hulu! "Fun, sexy and unputdownable—a classic."  —Marian Keyes "Flawlessly entertaining."  —Helen Fielding "Joyful and mischievous." —Jojo Moyes The glamorous, cutthroat world of 1980s British television is all about power, a time when the affluent elite existed in a bubble of immense wealth and influence, and would use any means to get what they wanted. Lord Baddingham is desperate to retain the Corinium TV franchise. And to do so, he’s hired Declan O’Hara, an Irish talk show mega-star. Baddingham has also enticed on board Cameron Cook, a gorgeous and brash executive, to produce Declan’s program. But Declan and Cameron detest each other, soon provoking a storm of controversy.   Enter into the fray everyone's favorite deliciously handsome, hate-to-love-him bad-boy, Rupert Campbell-Black. As a rival group emerges to pitch for the franchise, reputations ripen and decline, true love blossoms and burns, marriages are made and shattered, and everyone is competing—in bed and in the boardroom—to come out on top.